KARAKTERISTIK BETON BERONGGA RAMAH LINGKUNGAN DENGAN MATERIAL LOKAL DAERAH - Muhammad Ridho; Arbain Tata; Suyuti . (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2022)
Road construction generally uses flexible or rigid pavement that is impermeable to water. To prevent the problem of road damage caused by standing water, there are currently many new ways to control the flow of water on the pavement surface. One alternative in controlling water on the pavement surface is to use hollow concrete. This study aims to determine the effect of aggregate form in the hollow concrete mixture on the compressive strength and infiltration rate. The method used is the experimental method. The gravel aggregate used consists of 3 size variations which are a mixture of crushed stone and unbroken stone with sizes of 0.5-1 cm, 1-2 cm, and 2-3 cm, respectively. The water-cement factor (FAS) value used in the study was 0.40. The test was carried out at the age of 28 days of wet treatment. The results of the research that has been done, when viewed from its mechanical properties, this concrete has decreased compressive strength by 28-36%. The larger the size of the gravel aggregate used, the greater the decrease in compressive strength that occurs. For the value of the infiltration rate increased by 40-93%. The largest increase in infiltration rate values ​​occurred in the specimens using aggregate diameter with the largest size variation, namely 2-3 cm. The larger the size of the coarse aggregate used, the larger the cavity formed in the test object, the larger the cavity formed, then the ability of a test object to pass water (infiltration rate value) will be greater.